2005
DOI: 10.1016/j.ejheart.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of cardiac rehabilitation in elderly patients with heart failure

Abstract: Background: Heart failure, a condition predominantly affecting the elderly, represents an ever-increasing clinical and financial burden for the NHS. Cardiac rehabilitation, a service that incorporates patient education, exercise training and lifestyle modification, requires further evaluation in heart failure management. Aim: The aim of this study was to determine whether a cardiac rehabilitation programme improved on the outcomes of an outpatient heart failure clinic (standard care) for patients, over 60 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
1
22

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(194 citation statements)
references
References 22 publications
9
162
1
22
Order By: Relevance
“…Indeed, for rural patients, factors other than proximity to a program may influence attendance, such as the quality of roads and harsh weather in particular for northern-residing outpatients (Curnier, Savage & Ades 2005, Pell, Morrison 1998). Finally, heart failure patients reported that one of the reasons for nonattendance was anxiety over travel (Austin et al 2005).…”
Section: Other Geographic Barriers To Cr Utilizationmentioning
confidence: 99%
“…Indeed, for rural patients, factors other than proximity to a program may influence attendance, such as the quality of roads and harsh weather in particular for northern-residing outpatients (Curnier, Savage & Ades 2005, Pell, Morrison 1998). Finally, heart failure patients reported that one of the reasons for nonattendance was anxiety over travel (Austin et al 2005).…”
Section: Other Geographic Barriers To Cr Utilizationmentioning
confidence: 99%
“…[15][16][17] Many intervention programs have been developed and evaluated to improve self-management behavior in CHF patients. Some of these-such as telephone-or home-based interventions, [18][19][20] programs in clinical (outpatient) settings, [21][22][23] and groupbased programs [24][25][26] -have demonstrated positive outcomes on health-related quality of life. However, most intervention programs solely emphasize the medical aspects of CHF self-management (eg, symptom recognition), whereas patients face equal difficulties in dealing with the social and emotional consequences of CHF.…”
mentioning
confidence: 99%
“…In general, supervised CR programs are successful in increasing physical fitness, cardiovascular performance, quality of life and reducing mortality [5][6][7][8][9][10][11][12][13][19][20][21][22][23][24].However, there are indicat ions that only 11% to 30% of those who need CR have access to specialized centers [6,22,23,25].Taking these facts into consideration, there has been an increase in the number of programs, whether supervised or not. The effectiveness of these programs has been well documented, revealing broad benefits [19,23,[26][27][28],although other studies have failed to observe positive effects, especially those regarding quality of life [29].In the present study, patients with HF in both groups demonstrated improvement in cardio respiratory fitness and in functional capacity during the 60 intervention days, as verified by other authors [19][20][21]23,[26][27][28].Nevertheless, only the supervised CR group showed quality of life imp rovement along the 60 CR days.…”
Section: Supervised Program Effectsmentioning
confidence: 99%
“…Several studies have already demonstrated the efficacy o f exercise -based CR programs [7][8][9][10][11], but a meta -analysis of randomized controlled trials [12] has concluded that quality of life improves to similar levels in patients receiving CR and standard care.The aim of the present study was to evaluate the effectiveness of asupervised CR program in the quality of life of HF subjects, as compared to standard care. Success indicators were based on cardiorespiratory capacity analysis, functional capacity, quality of life, survival and/or mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation